PENAMBAHAN SISTEM KOMPUTERISASI PADA UNIVERSAL TESTING MACHINE DI JURUSAN TEKNIK MESIN POLITEKNIK NEGERI MALANG - Rafik Djoenaidi; Andri Setiawan; Martha Putri Indrayanti (Jurnal Energi dan Teknologi Manufaktur, 2021)
Rafik Djoenaidi, Andri Setiawan, Marthania Putri Indrayati ,. 2021. "Addition of Computerized Systems to Universal Testing Machines in the Department of Mechanical Engineering, State Polytechnic of Malang". Tensile testing equipment is an educational laboratory facility that is very important in supporting and supporting the teaching and learning process in the laboratory, especially the Tensile testing machine in the Polynema Mechanical Engineering department still uses manual reading of test results, along with the development of technology, currently the Tensile testing machine will equipped with digitalization tools and integrated into the computer with data acquisition. Tensile test equipment is an educational laboratory facility that is very important in supporting and supporting the teaching and learning process in the laboratory, especially the Tensile testing machine in the Polynema Mechanical Engineering department still uses reading test results manually, along with the development of technology, the current Tensile test machine will equipped with a digitizing device and integrated into a computer with data acquisition. The output of this tensile test is in the form of a tensile force table (F), elongation (ΔL), stress, strain and stress strain graph. The method for recording tensile force data (F) is done by connecting directly using a sonic scale type sp-320 and integrating it into a computer with data acquisition so that it can display a graph.. Keywords: Tensile test equipment, data acquisition, Sonic Scale